The Effect of Marketing Mix and Retail Mix on Consumer Loyalty of Gelael Supermarket in Makassar City - Annisa Mauliandini; Abdul Razak Munir; Abdul Rakhman Laba (SEIKO : Journal of Management & Business, 2019)
This research aims to determine the effect of marketing mix and retail mix on consumer loyalty. This research conducted in the company of PT. Gelael Indotim Makassar. The data used in this study were obtained from a questionnaire (primary). The sampling method uses purposive sampling method. The number of samples used was 160 customers from different gender, age and occupation. The analytical method used is Structural Equation Modeling (SEM) using Smart-PLS 2.0 for Windows. The research findings show that the variables of Marketing Mix has a positive yet not a significant effect on Consumer Loyalty of Gelael Supermarket, meanwhile Retail Mix has positive and significant effect or indirect effect. Keywords: Marketing Mix, Retail Mix, Consumer Loyalty, Gelael Supermarket.